Five minutes (that's a lot of time) (no, it's not) (yes, it is) - Scanlon, Elizabeth Garton; Vernick, Audrey (G. P. Putnam's Sons, 2019)
Throughout a child's day, five minutes can go by quickly (when you are on a roller coaster) or slowly (when you are in the dentist's chair).